Signal transduction in the footsteps of goethe and schiller. - Friedrich, K; Lindquist, J; Entschladen, F; Serfling, E; Thiel, G; Kieser, A; Giehl, K; Ehrhardt, C; Feller, S; Ullrich, O; Schaper, F; Janssen, O; et al. (2009)
The historical town of Weimar in Thuringia, the "green heart of Germany" was the sphere of Goethe and Schiller, the two most famous representatives of German literature's classic era. Not yet entirely as influential as those two cultural icons, the Signal Transduction Society (STS) has nevertheless in the last decade established within the walls of Weimar an annual interdisciplinary Meeting on "Signal Transduction - Receptors, Mediators and Genes", which is well recognized as a most attractive opportunity to exchange results and ideas in the field.The 12th STS Meeting was held from October 28 to 31 and provided a state-of-the-art overview of various areas of signal transduction research in which progress is fast and discussion lively. This report is intended to share with the readers of CCS some highlights of the Meeting Workshops devoted to specific aspects of signal transduction.